Relation of Depression, Anxiety, and Quality of Life with Outcome after Percutaneous Transluminal Coronary Angioplasty - Suprakash Chaudhury; Kalpana Srivastava (The Scientific World Journal)
Background. Despite, increasing number of percutaneous transluminal coronary angioplasty (PTCA) being performed, there is a paucity of Indian studies on the psychological effects of PTCA. Aim. To study the relation of anxiety, depression, and health related quality of life with outcome after PTCA. Methods. A total of 35 patients undergoing PTCA were included in the present project with their informed consent. All patients filled a specially designed proforma, the Hospital Anxiety and Depression Scale, Coronary Scale, Seattle Angina Questionnaire, and a health related quality of life measure (EQ 5D) one day before undergoing PTCA. Three days after PTCA patients were reassessed with the Hospital anxiety & depression scale, Seattle angina questionnaire and the EQ 5D. Results. Analysis showed that 46% had significant anxiety and 32.1% had significant depression before PTCA. Following successful PTCA, none of the patients had significant anxiety, and only 2 (3.6%) had significant depression. On the Seattle Angina Questionnaire, physical limitation reduced from 67.9 to 48. Disease perception improved from 21.2 to 37.1. On the EQ5D, the health status improved from 42.7 before PTCA to 78.7 after PTCA. Conclusion. Successful PTCA resulted in significant reduction in anxiety, depression, and physical limitation and improvement in disease perception and health status.